Does context matter? Unpacking differences in program quality and developmental experiences across competitive and recreational youth sport. Issue 5 (October 2021) - Bean, Corliss; Shaikh, Majidullah; Kramers, Sara; Forneris, Tanya
To date, little research has explored differences between competitive and recreational youth sport contexts beyond descriptions of inherent features. The purpose of this exploratory study was to examine if differences existed between competitive and recreational youth sport on (a) observed quality delivery and (b) youth's perceptions of basic psychological needs satisfaction and developmental experiences. Forty-six youth sport teams participated in the study from competitive ( n  = 23) and recreational contexts. This study adopted a multi-method approach of self-report questionnaires and researcher observations. Teams agreed to be involved in observations ( n  = 3), questionnaires ( n = 12) or both methods of data collection ( n  = 31). Quality was assessed through 216 observations ( n  = 134 competitive; Mper team  = 6.55), while basic psychological needs satisfaction and developmental experiences were examined through two questionnaires ( N  = 413) completed at season end. Descriptive statistics and MANOVAs were calculated for all measures and associated subscales. Results revealed non-significant differences between competitive and recreational programs, despite high scores across the three measures. Significant effects are discussed related to of coaches' years of coaching experience on program quality and ethnicity ratios on positive developmental experiences. Also discussed are notable effect sizes on opportunities for belonging and choice, where recreational contexts scored higher than competitive on each factor. Results offer understandings of how coach delivery can be enhanced, regardless of context, to optimize developmental benefits for youth. Implications are discussed for how future research can explore the complexities of different sport contexts, including associated coaching practices.